2015
DOI: 10.1042/bst20150041
|View full text |Cite
|
Sign up to set email alerts
|

Sustained NRF2 activation in hereditary leiomyomatosis and renal cell cancer (HLRCC) and in hereditary tyrosinemia type 1 (HT1)

Abstract: The nuclear erythroid 2-like 2 transcription factor (NRF2), is a major regulator of cellular redox balance. Although NRF2 activation is generally regarded as beneficial to human health, recent studies have identified that sustained NRF2 activation is over-represented in many cancers. This raises the question regarding the role of NRF2 activation in the development and progression of those cancers. This review focuses on the mechanisms and the effects of NRF2 activation in two hereditary cancer predisposition s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Activation of the Nrf2 pathway by phytochemicals may be of benefit in the prevention of cancer and absence of Nrf2 increases susceptibility of cells to cancer. However, on the flip side, excessive sustained Nrf2 activation is observed in many cancer cell types, particularly the lung, due to loss-offunction somatic mutations in Keap1 or gain-of-function 'hot spot' mutations in NFE2L2 that encodes Nrf2 [4,12]. Nrf2 can drive cell proliferation and inhibit apoptosis and enhance tumour development through metabolic reprogramming, including up-regulation of the pentose phosphate pathway.…”
Section: Nrf2 and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the Nrf2 pathway by phytochemicals may be of benefit in the prevention of cancer and absence of Nrf2 increases susceptibility of cells to cancer. However, on the flip side, excessive sustained Nrf2 activation is observed in many cancer cell types, particularly the lung, due to loss-offunction somatic mutations in Keap1 or gain-of-function 'hot spot' mutations in NFE2L2 that encodes Nrf2 [4,12]. Nrf2 can drive cell proliferation and inhibit apoptosis and enhance tumour development through metabolic reprogramming, including up-regulation of the pentose phosphate pathway.…”
Section: Nrf2 and Diseasementioning
confidence: 99%
“…Cancer cells also hijack the Keap1-Nrf2 pathway to enhance chemoresistance and radio-resistance. Large-scale multiomics projects in various cancer types are underway to identify mechanisms leading to increased Nrf2 activity in cancer [4,12,13].…”
Section: Nrf2 and Diseasementioning
confidence: 99%
“…Interestingly, NRF2 activation was also observed in FAH −/− mice (Marhenke et al , ), but the mechanism underlying NRF2 activation was not assessed. Sandhu predicted that FAA activates NRF2 by covalently modifying cysteine residues of KEAP1 (Sandhu et al , ). Because SA accumulated in HT1 as well, our MS/MS data suggested that SA may also contribute to NRF2 activation in FAH −/− mice via direct modification of KEAP1.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increased cellular glucose levels stimulate NADPH-mediated reactive oxygen species (ROS) production which can also directly stabilize HIF1 [32]. Excess HIF accumulates and results in increased transcription of multiple factors (VEGF, PDGF, GLUT, EGFR, glycolytic enzymes) which promote tumor growth and angiogenesis and support aerobic glycolysis [33,34]; 3) Excess fumarate also leads to activation of an oxidative stress response pathway mediated by NRF2, believed to be essential for cell survival in the context of redox imbalances resulting from Krebs cycle inactivation [35,36].…”
Section: Management Of Metastatic Renal Cancermentioning
confidence: 99%